BOOSTING SALES: EFFECTIVE PROMOTIONAL STRATEGIES IN CATFISH FARMING - Anam, Chairul; Zebua, Martin (ITB AAS Indonesia Surakarta, 2024)
Research in Desa Sidodadi, Bojonegoro, examined effective promotional strategies for enhancing catfish sales. Using qualitative interviews with farmers, it showed that utilizing social media and partnering with local vendors expanded consumer outreach and boosted product visibility. Digital marketing reduced distribution costs and facilitated direct customer interactions, leading to higher customer loyalty and satisfaction. Workshops and seminars raised public awareness about catfish benefits but highlighted dependencies on intermediaries and ineffective distributions needing improvement via better logistical arrangements. Analyzing SWOT helped farmers leverage strengths while mitigating weaknesses, opportunities, and threats effectively. Recommendations included upgrading digital technologies in marketing campaigns alongside educational sessions on modern marketing practices coupled with strategic alliances between farmers' cooperatives or individual producers with local retailers/restaurants aiming substantial increases in overall sale volumes.